The multicenter effectiveness study of inpatient and day hospital treatment in departments of psychosomatic medicine and psychotherapy in Germany - Doering, Stephan; Herpertz, Stephan; Pape, Magdalena; Hofmann, Tobias; Rose, Matthias; Imbierowicz, Katrin; Geiser, Franziska; Bierling, Antonie Louise; Weidner, Kerstin; Rademacher, Jörg; Michalek, Silke; Morawa, Eva; et al. (Frontiers in Psychiatry, 2023)
Background: Reliable outcome data of psychosomatic inpatient and day hospital treatment with a focus on psychotherapy are important to strengthen ecological validity by assessing the reality of mental health care in the field. This study aims to evaluate the effectiveness of inpatient and day hospital treatment in German university departments of Psychosomatic Medicine and Psychotherapy in a prospective, naturalistic, multicenter design including structured assessments.: Structured interviews were used to diagnose mental disorders according to ICD-10 and DSM-IV at baseline. Depression, anxiety, somatization, eating disorder and posttraumatic stress disorder (PTSD) symptoms, as well as personality functioning were assessed by means of questionnaires on admission and at discharge. Results: 2,094 patients recruited by 19 participating university hospitals consented to participation in the study. Effect sizes for each of the outcome criteria were calculated for 4-5 sub-groups per outcome domain with differing severity at baseline. Pre-post effect sizes for patients with moderate and high symptom severity at baseline ranged from d=0.78 to d=3.61 with symptoms of PTSD, depression, and anxiety showing the largest and somatization as well as personality functioning showing somewhat smaller effects. Conclusions: Inpatient and day hospital treatment in German university departments of Psychosomatic Medicine and Psychotherapy is effective under field conditions.